Great museums of the world (Renton, Wash. Topics Entertainment, 2003)
This CD-ROM allows the user to take a virtual tour of all the great art museums of Europe, including The Louvre, The Tate Gallery, The Hermitage, the Vatican museums, and many more.
Le Grand Louvre, v.1, The masterpieces -- Famous museums of Europe vols. 1 & 2.
Title from disc labels.
System requirements: Windows 95 and higher, including XP, 486 DX or better, 8MB RAM, 10MB HD, 640x480, 16-bit high colors, sound card, mouse.
Keywords: Musee du Louvre; Museums -- Europe; Museums -- History. -- Europe; Art museums -- Interactive multimedia. -- Europe